Cholesterol and presynaptic glutamate transport in the brain - Borisova, Tatiana (SpringerBriefs in Neuroscience, 2013)
Glutamate is the primary excitatory neurotransmitter in the CNS and disturbances in glutamate transport contribute to a number of neurological and neurodegenerative disorders.  Appropriate levels of cholesterol are very important for the proper functioning of glutamate transport while unbalanced levels of cholesterol have been implicated in the pathogenesis of disorders such as stroke, ischemia, traumatic brain injury, and neurotoxicity.   In the proposed book, the author presents data from the literature and from her own lab to address the extent to and way in which membrane cholesterol modulates presynaptic glutamate transport and whether lowering the level of cholesterol available can offer some neuroprotective benefits.